Penegakan Hukum Tindak Pidana Perdagangan Orang Di Wilayah Hukum Polresta Pulau Ambon Dan Pulau-Pulau Lease - Ibrahim, Driyano Andri; Toule, Elsa Rima Maya; Wadjo, Hadibah Zahra (Bacarita Law Journal, 2024)
TPPO cases that have occurred in the last 3 years in the jurisdiction of the Ambon Island Police and Lease Islands have increased. In 2021 there will be 3 cases, in 2022 there will be 5 cases, and in 2023 there will be 6 cases. On average, TPPO victims handled from 2021 to 2023 came from Maluku and outside Maluku. Various efforts have been made by the Ambon Island and Lease Island Police, including through law enforcement by applying strict criminal sanctions to perpetrators as regulated in Law no. 21 of 2007 for handling TPPO in its jurisdiction. This research uses an empirical juridical research method which is descriptive analysis, with data obtained through literature study and interviews, then the data is analyzed qualitatively to obtain legal certainty regarding law enforcement of criminal acts of human trafficking in the jurisdiction of the Ambon Island and Lease Island Police. Based on the research results, it was found that TPPO cases that occurred in the jurisdiction of the Ambon Island Police and Lease Islands were caused by several factors, including economic factors, lack of attention from the family, the lure of jobs with high salaries, and current lifestyle competition. This problem is used by perpetrators to recruit victims to gain profit. The victims were from Maluku and outside Maluku. There are those who are employed in karaoke rooms in Ambon City and there are also those who are used as prostitutes who are ordered online via the Michat application. In order to deal with this crime, the Ambon Island and Lease Island Police took law enforcement action against the perpetrators of TPPO. However, law enforcement is influenced by 2 factors, namely internal and external factors. Furthermore, enforcement of the TPPO law at the Ambon Island and Lease Island Police was carried out in the form of repressive measures so that 14 cases from 2021, 2022 and 2023 were all escalated to court. This repressive action is carried out as a last resort in enforcing criminal law (ultimum remedium) with the aim of providing a deterrent effect to perpetrators and suppressing the rate of increase in TPPO cases in the future as well as realizing legal certainty, benefit and justice.